2000
DOI: 10.1021/bi000468e
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties of Protein Disulfide Bond in Oxidized Thioredoxin and Lysozyme:  A Pulse Radiolysis Study

Abstract: We have studied the one-electron reduction of oxidized Chlamydomonas reinhardtii thioredoxin and compared it to that of hen egg white lysozyme, using CO(2)(*) (-) free radicals as reductants. This comparison shows that the thioredoxin disulfide/thiol redox couple has different properties than that of lysozyme: the disulfide radical pK(a) is much lower (around 5 for small disulfides, 4.62 for lysozyme, <3 for thioredoxin). To get a better understanding of the modulation of the thioredoxin redox properties we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Other studies using frozen solutions also show that solvent‐exposed parts of a protein are the most radiation‐sensitive (Filali‐Mouhim et al 1997; Audette et al 2000). However, sulfur‐containing groups differ not only in their solvent accessibility but also in their structural environment, which has been proposed to play an important role in defining the stability of a disulfide bond towards free radical attack (Ravelli and McSweeney 2000; Lmouméne et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies using frozen solutions also show that solvent‐exposed parts of a protein are the most radiation‐sensitive (Filali‐Mouhim et al 1997; Audette et al 2000). However, sulfur‐containing groups differ not only in their solvent accessibility but also in their structural environment, which has been proposed to play an important role in defining the stability of a disulfide bond towards free radical attack (Ravelli and McSweeney 2000; Lmouméne et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The most extensively studied group is that of sulfur-centered radical cations, but they can also be found in anions [7,21,25,26,29] or neutrals adducts [24,27,28,30,36]. Time-resolved pulse radiolysis techniques have demonstrated that particularly the sulfur-containing species exhibit strong optical absorption in the visible and near UV regions.…”
Section: Figurementioning
confidence: 99%
“…9A, control). Addition of thioredoxin, which is a scavenger of thiyl radicals (115), strongly increases the reaction rate at a delayed reaction time, that is, when the catalysis-associated inactivation becomes pronounced ( Fig. 9A).…”
Section: Figmentioning
confidence: 99%
“…Compared with thiyl radicals of monothiols, the thiyl radicals of dithiols are significantly more stabilized through their interconversion with the disulfide anion radical shown in Figure 7 (13). The disulfide anion radical exhibits reducing properties (E 0 = -1.6 V), while the thiyl radical is a strongly oxidizing species with E 0 from +0.75 to +1.33 V. The oxidizing potential depends on the tendency of the radical to be protonated (115). The protonation prevents the thiyl radicals of dithiols to close into the 3estructure of the moderate reductant, the disulfide anion radical (Fig.…”
Section: Fig 11mentioning
confidence: 99%
See 1 more Smart Citation